Crime in fact and fiction - Block, Brian P. (Waterside Press, 2015)
"This...book highlights differences in how crime is portrayed in the arts compared to reality, focusing on the roles of the police, courts and forensic investigators. Of interest to criminologists, sociologists, lawyers and other criminal justice personnel, it will also appeal to anyone interested in crime and punishment"--Back cover